2009
DOI: 10.1007/s10126-009-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Gymnodimine-A by High Performance Liquid Chromatography in Contaminated Clams from Tunisia Coastline

Abstract: Quantitative determination by high performance liquid chromatography (HPLC) was performed for gymnodimine-A (GYM-A), a phycotoxin responsible for the contamination of Tunisian clams. This study demonstrates a rapid and reproducible HPLC-ultraviolet (UV) method for extraction, detection and quantification of GYM-A in toxic clams. The extraction of GYM-A from the digestive gland of clams in acetone, subsequent clean-up with diethyl ether and extraction with dichloromethane is the more valid protocol. Chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…These results confirmed the previous reports of presence of GYMs in the Gulf of Gabes (Biré et al, 2002;Marrouchi et al, 2010), but also showed the great prevalence of this toxin group in the area. According to our results, synergistic effects with other lipophilic toxins proposed by Dragunow et al (2005) are unlikely.…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…These results confirmed the previous reports of presence of GYMs in the Gulf of Gabes (Biré et al, 2002;Marrouchi et al, 2010), but also showed the great prevalence of this toxin group in the area. According to our results, synergistic effects with other lipophilic toxins proposed by Dragunow et al (2005) are unlikely.…”
Section: Resultssupporting
confidence: 95%
“…Apparently, GYM-B is 10-fold less toxic than GYM-A (Kharrat et al, 2008), and a potential synergistic effect with other toxins has been proposed since GYMs were able to sensitize Neuro2a cells to other marine toxins such as okadaic acid (Dragunow et al, 2005). Nowadays, GYM-A has shown a worldwide distribution including New Zealand coastlines (Stirling, 2001b), Tunisia (Biré et al, 2002;Marrouchi et al, 2010), Australia (Takahashi et al, 2007), Europe & North America coast (Kharrat et al, 2008), and more recently South Africa (Krock et al, 2009) and China (Liu et al, 2011). They may persist in oysters for years (MacKenzie et al, 2002), although an enhanced detoxification capability has been recently demonstrated in clams (Medhioub et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A HPLC-UV method was developed for the routine analysis of GYMs in shellfish at a wavelength measuring up to 210nm and the LOD of GYM A was reported to be 2.4 μg/kg of digestive gland of clams (Marrouchi et al 2009). However, cyclic imines lack chromophores and, therefore, optical detection methods, such as ultraviolet (UV), do not provide sufficient selectivity because the UV absorption of cyclic imines is low (EFSA 2010).…”
Section: High Performance Liquid Chromatography With Ultra Violet Detmentioning
confidence: 99%
“…there is evidence that CIP toxins and their producers also are found in europe, the USA, and North Africa (Aasen et al, 2005a;Bire et al, 2002;Cembella and Krock, 2008;Ciminiello et al, 2006;John et al, 2003;MacKinnon et al, 2006;Marrouchi et al, 2010;Rundberget et al, 2011;touzet et al, 2008;Villar Gonzalez et al, 2006), and their presence, along with PSP to CTX also primarily in predatory fish consumed by humans (snapper, barracuda, amber jack and moray eel), and more investigations should be conducted on the role on Mtx in human intoxication.…”
Section: Ciguatera Fish Poisoning (Cfp) Toxinsmentioning
confidence: 99%